Deficits in axonal transport in hippocampal-based circuitry and the visual pathway in APP knock-out animals witnessed by manganese enhanced MRI - Gallagher, Joseph J. (2012)
Mounting evidence implicates axonal transport defects, typified by the presence of axonal varicosities with aberrant accumulations of cargo, as an early event in Alzheimer’s disease (AD) pathogenesis. Work identifying amyloid precursor protein (APP) as a vesicular motor receptor for anterograde axonal transport further implicates axonal transport in AD. Manganese-enhanced MRI (MEMRI) detects axonal transport dynamics in preclinical studies. Here we pursue an understanding of the role of APP in axonal transport in the central nervous system by applying MEMRI to hippocampal circuitry and to the visual pathway in living mice homozygous for either wild type or a deletion in the APP gene (n = 12 for each genotype). Following intra-ocular or stereotaxic hippocampal injection, we performed time-lapse MRI to detect Mn(2+) transport. Three dimensional whole brain datasets were compared on a voxel-wise basis using within-group pair-wise analysis. Quantification of transport to structures connected to injection sites via axonal fiber tracts was also performed. Histology confirmed consistent placement of hippocampal injections and no observable difference in glial-response to the injections. APP −/− mice had significantly reduced transport from the hippocampus to the septal nuclei and amygdala after 7 hours and reduced transport to the contralateral hippocampus after 25 hours; axonal transport deficits in the APP −/− animals were also identified in the visual pathway. These data support a system-wide role for APP in axonal transport within the central nervous system and demonstrate the power of MEMRI for assessing neuronal circuitry involved in memory and learning.